Environmental pollution evaluation and spatiotemporal distribution of different forms of phosphorus in a phosphate mining area in Western Hubei, China - Lei Kou; Junwei Zhang; Liyue Huang; Guanyu Chen; Shupeng Jiang; Ding Han; Dayuan Jiang (Heliyon)
Taking the typical phosphate mining area in Western Hubei as the research object, groundwater, surface water, soil and sediment in phosphate mining area were investigated and evaluated comprehensively to clarify the temporal and spatial distribution characteristics of different forms of phosphorus in phosphate mining area and reveal the migration and transformation of phosphorus. Results showed that whether in the dry season or the wet season, total phosphorus levels in groundwater (dry season from November to December 2021, 0.42 mg/L; wet season from August to September 2022, 0.24 mg/L) exceeded the standard index. The total phosphorus was related to seasonal changes and the distribution of phosphate rock. Particulate phosphorus was the main component of total phosphorus in surface water, and sediment phosphorus was one of the sources of phosphorus in surface water. The total phosphorus in surface water was strongly correlated with particulate phosphorus, and the correlation coefficient was 0.984. The main sources of phosphorus in surface water were exogenous input. The sediment had a certain contribution to the phosphorus in the water, but it was not the main factor. The correlation coefficients between sediment total phosphorus and water total phosphorus and particulate phosphorus were 0.349 and 0.346, respectively. The soil total phosphorus content was closely related to phosphate mining activities. The migration and transformation of phosphorus sources were mainly through soil leaching, scouring and mine drainage into surface water, and there may be migration of surface water to groundwater in monitoring wells. The correlation between total phosphorus in soil and groundwater was poor. The high content of total phosphorus in surface soil was not the main source of total phosphorus in groundwater. Rainwater scours the surface soil of the ore yard and the mine entrance, resulting in the loss of soil total phosphorus to the river, and the phosphorus in the soil may indirectly enter the groundwater.